Mirabegron for the treatment of overactive bladder: a prespecified pooled efficacy analysis and pooled safety analysis of three randomised, double‐blind, placebo‐controlled, phase III studies. Issue 7 (21st May 2013) - Nitti, V. W.; Khullar, V.; van, P.; Herschorn, S.; Cambronero, J.; Angulo, J. C.; Blauwet, M. B.; Dorrepaal, C.; Siddiqui, E.; Martin, N. E.
Summary Introduction To examine pooled efficacy data from three, large phase III studies comparing mirabegron (50 and 100 mg) with placebo, and pooled safety data including additional mirabegron 25 mg and tolterodine extended release (ER) 4 mg results. Methods This prespecified pooled analysis of three randomised, double‐blind, placebo‐controlled, 12‐week studies, evaluated efficacy and safety of once‐daily mirabegron 25 mg (safety analysis), 50 or 100 mg (efficacy and safety analyses) and tolterodine ER 4 mg (safety analysis) for the treatment of symptoms of overactive bladder (OAB). Co‐primary efficacy measures were change from baseline to Final Visit in the mean number of incontinence episodes/24 h and mean number of micturitions/24 h. Key secondary efficacy end‐points included mean number of urgency episodes/24 h and mean volume voided/micturitions, while other end‐points included patient‐reported outcomes according to the Treatment Satisfaction‐Visual Analogue Scale (TS‐VAS) and responder analyses [dry rate (posttreatment), ≥ 50% reduction in incontinence episodes/24 h, ≤ 8 micturitions/24 h (post hoc analysis)]. The safety analysis included adverse event (AE) reporting, laboratory assessments, ECG, postvoid residual volume and vital signs (blood pressure, pulse rate). Results Mirabegron (50 and 100 mg once daily) demonstrated statistically significant improvements compared with placebo for the co‐primary end‐points, key secondary efficacy variables, TS‐VAS and responder analyses (all comparisons p < 0.05). Mirabegron is well tolerated and demonstrates a good safety profile. The most common AEs (≥ 3%) included hypertension, nasopharyngitis and urinary tract infection (UTI); the incidence of hypertensive events and UTIs decreased with increasing dose. For mirabegron, the incidence of the bothersome antimuscarinic AE, dry mouth, was at placebo level and of a lesser magnitude than tolterodine. Conclusion The efficacy and safety of mirabegron are demonstrated in this large pooled clinical trial dataset in patients with OAB.